LEATHER SEWING : 8 New Projects for Leather Crafters of All Levels - Bothe, Carsten; Simulingua, Inc. (Atglen, Pennsylvania : Schiffer Publishing, Ltd., 2022)
"Leatherworking is a craft that is becoming more and more popular and is a hobby that you can get started without making any big expenditures or investment. Besides, it is fun! You can make unique, durable, and sustainable leather products in your kitchen. In a follow-up to his previous book, Practical Leatherwork, hunter and professional outdoorsman Carsten Bothe guides you with richly illustrated step-by-step instructions through sewing techniques, preparing and manipulating the leather, and eight beginner, intermediate, and advanced leatherworking projects, including a leather barbecue apron, dice cup, book cover, canteen, and more. Learn techniques like the saddle stitch and baseball stitch and how to sew chamois leather, wet molding, and sewing. Then you can take the skills you've mastered and create your own stunning sewn leather crafts!" -- From back cover.
Originally published as Leder nahen: Neue Projekte. Translated from the German by Simulingua, Inc.
Bibliography : page 109
Keywords: Leatherwork; Leather; Handicraft